PENGEMBANGAN MEDIA WEBSITE INTERAKTIF BERBANTUAN GOKALA UNTUK MENUNJANG PEMBELAJARAN MENDALAM PADA SISWA SEKOLAH DASAR - Intan Ayu Sekar Sari; Wahyuni, Indah Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop an interactive learning media named GOKALA (Google Site Karakteristik Wilayah Tempat Tinggal) to enhance students' understanding and engagement in the Pancasila Education subject for fifth-grade elementary school students. The research uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques include observation, interviews, expert validation, response questionnaires from teachers and students, as well as pretest and posttest results. The product was validated by material, media, and language experts, with average scores of 4.6, 4.46, and 3.9 respectively, categorized as very valid and valid. Response questionnaires indicate that teachers and students rated the media as very practical, with percentages of 86% and 93%. Effectiveness testing using pretest and posttest analysis resulted in an N-Gain score of 0.7078, categorized as high, with a 70.7% improvement in learning outcomes. These findings show that GOKALA is a feasible, practical, and effective digital platform to support interactive and meaningful learning in accordance with the Deep Learning Curriculum. This web-based media also enhances students' digital literacy and independent learning while making the learning process more engaging and contextual.